Benchmarking a Commercial (Sub-)THz Focal Plane Array Against a Custom-Built Millimeter-Wave Single-Pixel Camera - Sang-Hee Shin; Stepan Lucyszyn (IEEE Access, 2020)
For the first time, the characteristics of an evolving commercial camera technology that can operate at millimeter-wave frequencies has been independently investigated. In this work, we benchmark the TeraSense camera against a custom-built single-pixel camera at W-band, for image quality and aperture reflectance. It is found that the Tera-1024 TeraSense camera exhibits limited image resolution and fidelity, with significant levels of systematic spatial noise. In a poor signal-to-noise ratio scenario, the addition of random noise exacerbates these problems. Possible causes of both beam and image distortion have been identified in quasi-optical applications, which gives important insight into the best use of (sub-)THz cameras and interpretation of their images. Inherent standing waves caused by the significant power reflectance of the camera aperture is investigated in detail. A simple W-band one-port quasi-optical scalar network analyzer is developed, to determine the levels of reflectance for both cameras, with its bespoke calibration routine derived from first principles - providing a low-cost solution for many non-destructive testing applications. It is found that the TeraSense camera (with additional RAM) and single-pixel camera (having default RAM) have measured reflectance values of 27% and 3%, respectively, over a corresponding aperture area ratio of approximately 714:1. While our single-pixel camera provides excellent image resolution and fidelity, it inherently suffers from very slow raster-scanning speeds and operational bandwidth limitations. For this reason, the TeraSense camera technology is excellent for performing qualitative measurements in real time, with the caveats outlined in this paper.